Future prospects of biobased detergent derived from Jatropha c. seeds oil (JSO) - Said, N.; Nor Hidayah, Kamin; M. V., Sivaguru; Nur Syazwani, Ghazali; Mohamad Zaki, Sahad; Siti Farhana, Haron (AENSI Publishing, 2017)
Commercialized detergents are synthesized by using either branched-chain alkylbenzenesulfonate (ABS) or linear chain alkylbenzenesulfonate (LABS) which contributes to environment issues. To alleviate these issues, Jatropha c. seeds oil (JSO) was used as a potential feedstock of biobased detergent (biodetergent) synthesis. The JSO utilization as non-petroleum sources using potassium hydroxide-hydrogen peroxide technique (POHYPET) was conducted at 40°C. After pretreatment and analysis of JSO, the hydrogen peroxide and sulphuric acid were mixed in a bath stirrer flask. The pH was also controlled, and the added hydrogen peroxide was maintained until the foam quieted down. Objective: This work aimed to synthesize biodetergent from non-edible JSO containing fatty acid as a promising raw material. Effects of processing time, temperature and alkaline concentration on Jatropha c. seed oil biodetergent (JASOB) yield were also investigated. Results: The highest biodetergent yield (88%) was found at the potassium hydroxide concentration of 0.8 M, treatment time of 2 h and operation temperature of 80°C. The physicochemical properties of the examined JASOB was indicated at the foam height (0.7-2.3), emulsification with oil (D), hard water interface (L) and pH (8-9). These performances of JASOB fulfilled the required essential criteria of detergent standard. Conclusion: The obtained JASOB using POPYHET provides impactful results compared another biosurfactants sources, and the prospects of JSO can be deliberated as a renewal of fossil derived surfactants for future biodetergent.